2013
DOI: 10.1111/jpi.12047
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves the reprogramming efficiency of murine‐induced pluripotent stem cells using a secondary inducible system

Abstract: This study focused on the effect of melatonin on reprogramming with specific regard to the generation of induced pluripotent stem cells (iPSCs). Here, a secondary inducible system, which is more accurate and suitable for studying the involvement of chemicals in reprogramming efficiency, was used to evaluate the effect of melatonin on mouse iPSC generation. Secondary fibroblasts collected from all-iPSC mice through tetraploid complementation were cultured in induction medium supplemented with melatonin at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
1
18
0
1
Order By: Relevance
“…Melatonin has been known as a pleiotropic molecule. It is a potent free radical scavenger and antioxidant , and it also regulates cell proliferation and differentiation . Both melatonin membrane receptors 1 (MT1) and 2 (MT2) are G protein‐coupled receptors and regulate the activation of adenylate cyclase (AC) and phospholipase C (PLC) .…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has been known as a pleiotropic molecule. It is a potent free radical scavenger and antioxidant , and it also regulates cell proliferation and differentiation . Both melatonin membrane receptors 1 (MT1) and 2 (MT2) are G protein‐coupled receptors and regulate the activation of adenylate cyclase (AC) and phospholipase C (PLC) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown evidences that melatonin can enhance the production of iPSCs due to its antioxidant activity [8, 9]. In human adult MSCs, for instance, melatonin combined with the extracellular matrix can enhance cellular alkaline phosphatase (AP) activity, induce osteogenesis via the melatonin receptor 2 (MT2), and also reverse stress-induced MSC injuries [1013].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that melatonin supplementation enhances the quality of porcine embryos (Do et al, ) and bovine cloned embryos (Su et al, ). Melatonin supplementation also significantly improved the reprogramming efficiency of murine induced pluripotent cells (Gao et al, ). We therefore, asked if melatonin could enhance the derivation and maintenance of ESCs from rabbits using established methods.…”
Section: Introductionmentioning
confidence: 99%